Respuesta :
Step-by-step explanation:
3(x-1) -5(x-4) = 8
3x-3 -5x+20 = 8
3x -5x -3 +20 = 8
-2x + 17 = 8
17 -8 = 2x
9 = 2x
2x = 9
x = 9/2
Answer:
3(x-1)-5(x-4)=8
We move all terms to the left:
3(x-1)-5(x-4)-(8)=0
We multiply parentheses
3x-5x-3+20-8=0
We add all the numbers together, and all the variables
-2x+9=0
We move all terms containing x to the left, all other terms to the right
-2x=-9
x=-9/-2
x=4+1/2
3(x-1)-5(x-4)=8
We move all terms to the left:
3(x-1)-5(x-4)-(8)=0
We multiply parentheses
3x-5x-3+20-8=0
We add all the numbers together, and all the variables
-2x+9=0
We move all terms containing x to the left, all other terms to the right
-2x=-9
x=-9/-2
x=4+1/2